Efektifitas Penerapan Strategi Genius Learning Dalam Meningkatkan Prestasi Belajar Fiqih Siswa Kelas X MA. Al-Aman Payaman Solokuro Lamongan - Muh. Layyin farihin (Jurnal Pendidikan Islam, 2019)
Abstract: The educational concept was even more important when a person has to enter the life in society and the workplace. Due concerned should be able to apply what is learned in school to deal with problems encountered in daily life today and tomorrow. Education is a systematic process to improve the human dignity of a holistic manner, which enables students to develop optimally. Thus, education should be a strategic vehicle for efforts to develop all the potential of the individual, so that the goal of building a complete Indonesian man can be achieved. This type of research to study "Effectiveness application Genius Learning Strategy (intelligent learning) in increasing student achievement of class X MA Al-Aman Payaman Solokuro Lamongan" is a survey research (research field or Field Research).The data source is the subject from which the data can be obtained. The source of the data in this study are:field research Namely data obtained from the field research, while in this study the data is drawn from two sources: Human Covers the principal, educator teacher council, TU, and the students of class X in place Genius Learning Strategy research. Non-human Non-human data that is obtained by recording or viewing documents on the history of the founding of the institution, its organizational structure, the number of facilities, conditions of teachers, students and others. Results showed that student achievement enough, it is evident from the results of a questionnaire study using a questionnaire that writers spread to 38 respondents showed a percentage of 41%, provided students work on assignments given by teachers, timely in completing the task, the students apply the material in everyday life, students are able to understand the material identified by teachers, students play a role in the learning process jurisprudence, students answer questions posed by the teacher and friends, the students respond to the thoughts of teachers and friends, students critical in responding to problems related to Fiqh subject areas, and the value of the field of study Fiqh good student.